Optimal mirror deformation for multi conjugate adaptive optics systems. (28th January 2016) - Raffetseder, S; Ramlau, R; Yudytskiy, M
Abstract: Multi conjugate adaptive optics (MCAO) is a system planned for all future extremely large telescopes to compensate in real-time for the optical distortions caused by atmospheric turbulence over a wide field of view. The principles of MCAO are based on two inverse problems: a stable tomographic reconstruction of the turbulence profile followed by the optimal alignment of multiple deformable mirrors (DMs), conjugated to different altitudes in the atmosphere. We present a novel method to treat the optimal mirror deformation problem for MCAO. Contrary to the standard approach where the problem is formulated over a discrete set of optimization directions we focus on the solution of the continuous optimization problem. In the paper we study the existence and uniqueness of the solution and present a Tikhonov based regularization method. This approach gives us the flexibility to apply quadrature rules for a more sophisticated discretization scheme. Using numerical simulations in the context of the European extremely large telescope we show that our method leads to a significant improvement in the reconstruction quality over the standard approach and allows to reduce the numerical burden on the computer performing the computations.